On the antitrust economics of the electronic books industry - Germain Gaudin; Alexander White (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2014)
When Apple entered the ebook market, prices rose. A recent court decision found Apple guilty of colluding with publishers, blaming the price hike, in part, on agency agreements and prohibiting their use. Building a model to compare these with traditional wholesale agreements, we identify a single, pivotal condition that leads prices under agency to be higher than under wholesale with two-part tariffs but lower with linear pricing. Our model shows that the increase in ebook prices can be explained, instead, by heightened competition for reading devices, and it guides our understanding of when restricting agency agreements is advisable.
Keywords: D21; D40; L23; L4; L42; L51; L82; L86; 330; Electronic Books; Antitrust in High-Tech Industries; Vertical Contracting; Wholesale vs. Agency Agreements; Media Economics